PENGARUH RELATIONSHIP MARKETING TERHADAP CUSTOMER LOYALTY DI PT. MPM FINANCE CABANG PANAM PEKANBARU - Putra Budi Ansori (Universitas Muhammadiyah Jambi, 2018)
This research was conducted in the research conducted at PT MPM Finance, branches of Panam Pekanbaru, HR Soebrantas KM 12 No:A7 Pekanbaru City in 2017. Research aims to understand the influence of relationship marketing to customer loyalty in PT.MPM finance the branches of panam pekanbaru. The population in this study is 8,943 consumers who at PT MPM Finance, branches of Panam Pekanbaru, Then the number of samples is rounded to 99 consumers, after calculated by the Slovin formula. The sampling technique was done by accidental sampling. It means respondents (a subject) selected by chance alone from members of the population who are willing to are only sampled.From the analysis of single linear regression equation was formulated: Y= 7,988 + 0,639X .Where, constant at 7,988, meaning that if the variable Relationship Marketing is 0, then the dependent variable Relationship Marketing of 7,988 and a regression coefficient of variable variable Relationship Marketing amounted to 0,639, which means that if the Customer Loyalty increased by 1 point, then the Customer Loyalty also will be increased by 0,639. The coefficient is positive, meaning a positive relationship between the Relationship Marketing of the Customer Loyalty. The higher the Relationship Marketing the increasing Customer Loyalty. Based on test result of significant test (t), obtained t count value for independent variable of Relationship Marketing (X) is 12,486. The t table value with df = 99-2 and the 5% or 0.05 confidence level, is 1.98472. From these values can be concluded t count > t tabel means, there is a significant relationship or influence between Relationship Marketing to the Customer Loyalty of PT MPM Finance, branches of Panam Pekanbaru. Obtained value of R2 or R Square equal to 0,616 or 61,6%. This value can be interpreted that changes in the value of Customer Loyalty are influenced by changes in the value of free Relationship Marketing by 61,6 % while 38,4% is determined by other variables that do not exist in this research model. Keyword : Relationship Marketing, Customer Loyalty